WASP (Write a Scientific Paper): Recruitment for research. (September 2018) - Mallia, Pierre
Abstract: The recruitment of patients must occur in accordance with approved standards. Speaking to a patient during a routine clinical consultation and offering to participate in a research, even if consented to, can only be an introduction to the recruitment process. The potential participant must then be referred to a competent person who explains the reasons for the research, why the patient is a good candidate, what the requirements from the participant will be, such as any additional visits and blood samples to be taken, how long the research will last, any compensation and what type of research is to be undertaken, such as a double blind-controlled trial and what it means. Participants must be given due time to reflect, discuss with friends or relatives, and have a contact person and number to be free to ask any questions. Their rights during the research have to be explicitly described and the extent to which the data is anonymised and protected must be explained realistically. Compensation moreover must be fair and not too enticing that it will cloud the judgement of the participant to volunteer. As the name implies the participant must remain a volunteer.